The influence of temperature and types of filter media on the palm oil mill effluent (POME) treatment using the hybrid up-flow anaerobic sludge blanket (HUASB) reactor - Habeeb, Sinan Abood (2012)
Anaerobic wastewater treatment has been introduced as a clean technology due to its efficient feasibility for the treatment of high strength wastewater. It is now implemented in many tropical countries especially in Malaysia. However, some operational parameters are still under research and required additional knowledge. This research was thus conducted using the hybrid up-flow anaerobic sludge blanket (HUASB) reactor packed with oil palm shell (OPS) as filter material, for the biological treatment of palm oil mill effluent (POME). This research aimed at investigating the effects of temperature, type of filter media and sludge bed development on the system treatment efficiency. Long term operation (233 days) was conducted using three reactors operated at several temperatures (26-61°C) and organic loading rates (from 1.87 to 14.06 kg COD. m-3 .day-1 ), in order to assess the optimal treatment conditions. The feasibility of OPS was deeply investigated, where results showed favourable characteristics of OPS such as lightweight material (Specific gravity of 1.18), relatively high porous material (porosity of 26%), high specific surface area (0.205 m2 .g -1 ), rough surface (according to the SEM examination) and very high organisms’ adherence of 26 to 34%. The average removals of the parameters tested were: 80% COD, 65% total solids, 80% total suspended solids, 85% volatile suspended solids, 53% total nitrogen, 45% total phosphorus, 48% colour and 56% turbidity at specific conditions (temperature ranges 37-58°C packed with OPS material). The sludge bed development was also studied. According to the overall results obtained in this study, the operated system could reflect a feasible alternative system that can be successfully adapted by the palm oil plantations for cleaner environment and process.